Application of Herbal Meatball Processing Technology to Increase Stamina Against Covid 19 for the Wua Wua Subdistrict, Kendari City - Hafid, Harapin; Nuraini, Nuraini; Asminaya, N S; Aka, R; Fitrianingsih, Fitrianingsih; Toba, R D S; Kimestri, A B; Ananda, S H (Talenta Publisher Universitas Sumatera Utara, 2020)
Meatballs are one of the processed meat products that can be added by Moringa leaves in the manufacturing process. Moringa leaves contain a lot of protein, vitamins, and minerals. With the addition of Moringa leaves, in addition to increasing the nutritional value of meatballs, it also increases the potential of the foodstuff and can produce products that are of high nutritional value but are economical because Moringa leaves are cheap and easily available. The method used in the first community service program is to approach, interview and deepen problems and find solutions to problems. Second, using the method of learning by doing with teaching media in the form of a guide book on how to make herbal meatballs, giving brochures and demonstrations and banners that attract the interest of the community. Providing counseling and training by providing training and demonstration material or practice how to make herbal meatballs. Outcomes of this community service program 1) Increasing the competitiveness of the business of animal origin food products with herbal raw materials, 2) Increasing the turnover of community groups such as, improving values ​​in the community, 3) Providing additional knowledge to the public about processing livestock products (herbal meatballs) , 4) Producing products that can be useful to maintain fitness and body immunity so as to reduce the risk of exposure to covid-19.